PENGAWASAN PEMERINTAH KOTA TERHADAP USAHA INDUSTRI BATU BATA DI KOTA PEKANBARU TAHUN 2010-2013 - SYAHRONI "; ISHAK " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The rapid development of the city of Pekanbaru today we can see from the many infrastructure development in almost all regions of the Provincial Capital. With the rapid development of the construction would affect the increase in demand for building materials. One of the raw materials of the building is brick. It is utilized by most people,in the city of Pekanbaru, especially in Sail region Tenayan Raya sub-district. Phenomena occurring in the field is not only a positive impact generated solely by the efforts of industrial but also the negative impact is also important. Hence the need for intensive monitoring effort so that the brick industry in the city of Pekanbaru this could well ordered.The purpose of this study was to see how the oversight efforts undertaken by the Government of the city of Pekanbaru On brick Industry Effort and what factors are an obstacle in the implementation of the surveillance . This study uses qualitative methods with data collection techniques include observation, interview and questionnaire which is then processed and analyzed. Analysis of these data the author uses descriptive analysis tools are then presented in the form of a table of percentage as well as the description of logical expressions explanation in order to be understandable and comprehensible.Based on the results of research that the control conducted by the Government of the city of Pekanbaru, in this case the Department of industry and trade through Observation, Inspection and Reporting still less done. This is due to the presence of constraints that become obstacles in the implementation of the supervision of which is the human resources, rules (regulation), facilities and infrastructure.Keywords : City Government, Control, Industrial Business